Pengembangan Menu Unggulan Modern Berbahan Baku Lokal untuk Cafe di Wisata Rainbow Garden Poetoek Soeko Trawas Kabupaten Mojokerto - Mukti, Yayon Pamula; Tandelilin, Elsye; Eka Jayani, Nikmatul Ikhrom; Rani, Karina Citra (LP2M INSURI Ponorogo, 2023)
Poetoek Soeko Rainbow Garden Tour is one of the tourism attractions managed by BUMDES Sukosari Makmur in Trawas-East Java that provide beautiful flower garden objects. The presence of a café is one of the supporting factors of rainbow garden tourism. To give characteristics and improve visitor interest, café menu diversification based on local possibilities must be established. Local potential in the form of spice, tuber and local plants was cultivated through the Matching Fund community service initiative started by UBAYA in the form of instruction in the manufacturing of local-modern fusion food. Participatory Action Research (PAR) method was implemented and delivered in three stages: planning, execution, assessment, and monitoring. This community service initiative resulted in three variations of local-modern cuisine which are implemented in new menu book in the Poetoek Soeko Rainbow Garden café. This program had a beneficial influence on boosting the partners' knowledge and abilities, as evidenced by an examination of test scores before and after the training. Cooking competitions held after product creation not only measure participant skill, but also boost competitiveness in the development of future menus. Based on post-test conducted resulting the increase of knowledge regarding local ingredients and processing up to 15.63%.